Speech and computer : 19th International Conference, SPECOM 2017, Hatfield, UK, September 12-16, 2017, Proceedings /: 19th International Conference, SPECOM 2017, Hatfield, UK, September 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available